2011
DOI: 10.1016/j.jacc.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The CONNECT (Clinical Evaluation of Remote Notification to Reduce Time to Clinical Decision) Trial

Abstract: Wireless remote monitoring with automatic clinician alerts as compared with standard in-office follow-up significantly reduced the time to a clinical decision in response to clinical events and was associated with a significant reduction in mean length of CV hospital stay. (Clinical Evaluation of Remote Notification to Reduce Time to Clinical Decision [CONNECT]; NCT00402246).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
352
1
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(382 citation statements)
references
References 21 publications
(19 reference statements)
15
352
1
14
Order By: Relevance
“…4), given the association of atrial fibrillation with congestive heart failure and stroke. Atrial high-rate episodes are the most common arrhythmia recorded by wireless devices [8,9]. It has previously been shown that atrial high-rate episodes lasting ≥5 min double the risk of stroke or death in patients with sinus node dysfunction who undergo dual-chamber pacemaker implantation [10].…”
mentioning
confidence: 99%
“…4), given the association of atrial fibrillation with congestive heart failure and stroke. Atrial high-rate episodes are the most common arrhythmia recorded by wireless devices [8,9]. It has previously been shown that atrial high-rate episodes lasting ≥5 min double the risk of stroke or death in patients with sinus node dysfunction who undergo dual-chamber pacemaker implantation [10].…”
mentioning
confidence: 99%
“…[50][51][52][53] Direct pulmonary artery pressure device monitors have had promising results in the management of heart failure. The CardioMEMS TM device by St Jude Medical (Atlanta, GA, USA) is placed in the pulmonary artery during a right heart catheterisation and allows for measurement of pulmonary artery pressures.…”
Section: Strategies To Guide Diuretic Titrationmentioning
confidence: 99%
“…Este Grupo de Trabajo respalda ese documento y considera que hay evidencia suficiente para hacer la siguiente recomendación [174][175][176] .…”
Section: Control a Distancia De La Arritmia Y Del Dispositivounclassified